2022
DOI: 10.1007/s44206-022-00030-2
|View full text |Cite
|
Sign up to set email alerts
|

Sovereignty in the Digital and Contact Tracing Apps

Abstract: Recently, the concept of sovereignty in the digital has attracted much attention. Several publications dealing with this concept assume that it can best be described as a network of different, overlapping exercises of power. Nevertheless, there is a need for further research on how exactly sovereignty in the digital can be understood. In order to contribute to a better understanding of this concept, I illustrate its complex structure using contact tracing apps as a paradigmatic example. I conduct a narrative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 75 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The stronger the national borders and sense of belonging, the greater the marginalization of those in between borders and on the margin. Empirical studies have revealed the exclusion and stigmatization of marginal groups, such as non‐citizens and those who do not conform to national regulations during the pandemic crisis (James & Valluvan, 2020; Kloet et al, 2020; Orgad & Hegde, 2022; Tretter, 2023). According to these studies, the COVID‐19 pandemic resulted in the resurgence of nationalist sentiments, reinforcing the binary opposition of the nationally defined “us” versus “others” (Jasanoff et al, 2021).…”
Section: Digital Governmentality and Nationalismmentioning
confidence: 99%
“…The stronger the national borders and sense of belonging, the greater the marginalization of those in between borders and on the margin. Empirical studies have revealed the exclusion and stigmatization of marginal groups, such as non‐citizens and those who do not conform to national regulations during the pandemic crisis (James & Valluvan, 2020; Kloet et al, 2020; Orgad & Hegde, 2022; Tretter, 2023). According to these studies, the COVID‐19 pandemic resulted in the resurgence of nationalist sentiments, reinforcing the binary opposition of the nationally defined “us” versus “others” (Jasanoff et al, 2021).…”
Section: Digital Governmentality and Nationalismmentioning
confidence: 99%
“…Similar approaches have recently been examined in the context of the international deployment of DCT apps [23]. Following Floridi [22], Tretter [24] illustrates that this network is determined by 3 actors: the governments, each of which develops its own DCT app while establishing individual standards for data storage and digital surveillance; the tech companies, such as Google and Apple, which provide, but can also withdraw, the digital infrastructure to implement these apps and thus essentially have access to the data generated through smartphones; and the individuals who are at the core of DCT and whose behavior forms the basis for digital pandemic response.…”
Section: Data Sovereigntymentioning
confidence: 99%